Group Intensive Cognitive Activation in Patients with Major or Mild Neurocognitive Disorder - Panerai, Simonetta; Tasca, Domenica; Musso, Sabrina; Catania, Valentina; Ruggeri, Federica; Raggi, Alberto; Muratore, Stefano; Prestianni, Giuseppina; Bonforte, Cinzia; Ferri, Raffaele (Frontiers in Behavioral Neuroscience, 2016)
Background: No standard protocols are available for cognitive rehabilitation in conditions like Major or Mild Neurocognitive disorder (M-NCD or m-NCD, respectively); however, preliminary data seem to indicate that such interventions might have cost-effective beneficial effects and are free from side effect or adverse events. Three basic approaches are known: cognitive stimulation, cognitive training, and cognitive rehabilitation. Objective: Aim of this study was to assess the efficacy of a protocol of Group Intensive Cognitive Activation (g-ICA) in patients with both M-NCD and m-NCD; the protocol was specifically arranged in our Research Institute, based on the principles of the central role of the patient and the mediation pedagogy. Subjects and Method: Sixteen patients with M-NCD and fifteen patients with m-NCD were enrolled, as well as 11 patients with M-NCD who were used as a control group. The intervention was carried-out by a clinical neuropsychologist with daily group sessions over a period of two months. Neuropsychological assessment was performed at baseline and after the completion of the rehabilitative intervention. Results: General cognitive functioning, attention, ideomotor praxis and visual memory scores were found to be significantly increased in all patients. Beneficial and significant effects were also found for constructive praxis in M-NCD and for executive functioning in m-NCD. All areas of the language function were significantly ameliorated in m-NCD, while this happened only for verbal repetition and syntax-grammar comprehension in M-NCD. No changes were detected for long- and short-term verbal memory, which were found to be worsened in controls without activation. Conclusion: Our findings seem to indicate that g-ICA might be effective in inducing beneficial changes on the general cognitive functioning and other specific functions in patients with both m-NCD and M-NCD. Moreover, the specific protocol proposed, even if susceptible of important improvement, is easy to carry out within hospital facilities and cost-effective.